Development of Garcinia Atroviridis Capsule Towards Safe, Quality and Efficacious Product - MN, Noor Rasyila; MS, Zamree; MH, Nurhazwani; MA, Nor Azah; AL, Tan; Y, Norulaiman; R, Adib Zubaidi; A, Mohd Hafiz Hadi; A, Mohd Faizal; M, Juliza; S, Rohana (EDUCATUM Journal of Science, Mathematics and Technology, 2017)
Malaysia is one of the countries that has a rich diversity of underutilized fruits that grow wild in the region of Peninsular Malaysia, Sabah and Sarawak. One of them is Garcinia atroviridis or Asam gelugor. The crude extracts of the leaf and fruit possess predominantly antibacterial, antifungal, free-radical scavenging, anti-inflammatory activity and also reduces body weight. The use of Garcinia has been rapidly growing in the United States due to the desire of people to lose weight. Losing weight can be a challenge for many people. While most experts agree that a combination of proper diet and exercise is the best way to go, there are things that can be done to speed up the process. Herbs are good for speeding up the metabolism, aiding in digestion and energizing, so the output will be more intensity. Previous study found that aqueous extract of Garcinia atroviridis fruit significantly reduced the body weight of rats. Due to its potentiality to be developed as pharmaceutical and herbal medicine, this study was conducted to enhance the quality of herbal products produced through the research and development offered by FRIM. FRIM is very much concerned and aware of the implementation of three main aspects which are quality, safety and efficacy that is often emphasized by the Ministry of Health Malaysia (MOH) under the Food Safety & Quality Division and the National Pharmaceutical Regulatory Agency (NPRA) on herbal products marketed. The product development for formulating and producing capsule activities are initiated by looking into ethno-botanical information of herbal used, chemical and biological analysis, formulation of products and product performance and lastly IPQC testing and safety study. It is hoped that this study will produce herbal products with better quality as well as complying with the standards and able to penetrate into the global market.